2017
DOI: 10.5312/wjo.v8.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine and chondroitin for the treatment of osteoarthritis

Abstract: The prevalence of primary or idiopathic osteoarthritis (OA) of knee and hip joints has substantially increased in general population during the last decades. Analgesics and non-steroidal anti-inflammatory drugs are currently extensively used as non-surgical treatment options. However, they act as symptomatic treatments, not offering a cure of OA and they are accused for an increased risk of adverse events. Glucosamine (GL) and chondroitin (CH) are nutritional supplements that have recently gained widespread us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 84 publications
1
37
0
3
Order By: Relevance
“…The anti‐inflammatory activity of the Devil's claw may be critical in the symptomatic treatment of osteoarthritis (Brien et al., ) but, also, glucosamine and chondroitin are nutritional supplements which have recently gained widespread use as per os treatment options for OA. There is evidence supporting that both these compounds reach and retain a certain concentration in plasma and in joint fluid and cartilage (Innes, Clayton, & Lascelles, ; Persiani et al., ; Vasiliadis & Tsikopoulos, ). Moreover, also Boswellia serrata , mainly because of its boswellic acids, is already known as a mediator in various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐inflammatory activity of the Devil's claw may be critical in the symptomatic treatment of osteoarthritis (Brien et al., ) but, also, glucosamine and chondroitin are nutritional supplements which have recently gained widespread use as per os treatment options for OA. There is evidence supporting that both these compounds reach and retain a certain concentration in plasma and in joint fluid and cartilage (Innes, Clayton, & Lascelles, ; Persiani et al., ; Vasiliadis & Tsikopoulos, ). Moreover, also Boswellia serrata , mainly because of its boswellic acids, is already known as a mediator in various inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It can effectively relieve pain, but cannot effectively prevent longterm recurrence of the disease [2]. Glucosamine sulfate, a naturally occurring amino sugar in the matrix of cartilage, effectively repairs damaged soft tissue and inhibits the recurrence of inflammation [3]. Previous studies have shown that a combination of celecoxib with glucosamine sulfate could effectively control inflammatory response and reduce its long-term recurrence [4].…”
Section: Introductionmentioning
confidence: 99%
“…Glucosamine hydrochloride (C 6 H 13 NO 5 ; GlcN.HCl), an amino monosaccharide and important precursor for glycoprotein and lipid biosynthesis, is present in almost every human tissue and most abundant in the cartilage, connective tissue, intervertebral discs and synovial fluid . Glucosamine is the most important component for the synthesis of hyaluronic acid (HA) and chondroitin, the important constituents of articular cartilage and synovial fluid synthesis …”
Section: Introductionmentioning
confidence: 99%